Dynamics of the flora of windbreaks in the agricultural landscape of steppes in southern Ukraine - Sudnik-Wójcikowska, Barbara; Moysiyenko, Ivan; Slim, Pieter A. (Biodiversity: Research and Conservation, 2006)
Floristic studies were conducted in selected fragments of forest belts and adjacent abandoned fields in the fescue/feather-grass and wormwood/sod-grass steppe zones in Kherson and Mykolayiv provinces (southern Ukraine). Protective forest belts (windbreaks) have been planted in Ukraine since the 19th century. They constitute a conspicuous anthropogenic element of the woodless area in the present agricultural landscape of southern Ukraine (in Kherson Province their total length is estimated at 30 000 km). Windbreaks play not only an economic but also an ecological role (e.g. as ecological corridors). At present some of the forest belts are in poor condition and some of the trees have been cut or died. As a result, steppe species colonize some of the gaps in neglected forest stands. These species migrate from areas where anthropogenic influences are minimal, e.g. verges of river valleys, ravines, canyons, ‘balkas’, kurgans. It is estimated that the dendroflora of windbreaks includes about 80 species. In the fescue/feather-grass steppe zone, tree species like Elaeagnus angustifolia, Ulmus pumila, Gleditsia triacanthos and Cotinus coggygria, are the most expansive and frequently escape into the wild. Among the self-sown trees, Elaeagnus angustifolia is the dominant species in the wormwood/sod-grass steppe zone. In recent years the increasing area of abandoned and less intensively managed cultivated fields as well as limited grazing have been responsible for the intensification of the spread of alien tree species outside the windbreaks. Moreover, the anthropogenic transformation of the soil cover and perhaps the tendency for the climate to become more humid (which has been registered by climatologists for the last 25 years), facilitate the expansion of trees.